2021
DOI: 10.3389/fimmu.2021.749979
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation of Mast Cells by Estrogen via the Nuclear-Initiated Signaling Pathway Contributes to the Development of Endometriosis

Abstract: Endometriosis is an estrogen-dependent gynecological disease. The pathogenesis of endometriosis remains controversial, although it is generally accepted that the inflammatory immune response plays a crucial role in this process. Mast cells (MCs) are multifunctional innate immune cells that accumulate in endometriotic lesions. However, the molecular mechanism by which estrogen modulates MCs in the development of endometriosis is not well understood. Here we report that estrogen can induce the expression of NOD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…MCs are closely involved with IC severity in UB (51). Interestingly, a recent study showed that activation of MCs by NLRP3 contributed to the development of endometriosis (54). Further, high levels of infiltration by MCs occur in response to the damage to bladder integrity due to frequent urinary toxicity in IC (55).…”
Section: Discussionmentioning
confidence: 99%
“…MCs are closely involved with IC severity in UB (51). Interestingly, a recent study showed that activation of MCs by NLRP3 contributed to the development of endometriosis (54). Further, high levels of infiltration by MCs occur in response to the damage to bladder integrity due to frequent urinary toxicity in IC (55).…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of IHC score was examined by two histopathologists blinded to the protocol. The IHC scores are graded as follows: the staining intensity (0, no staining; 1, weak staining; 2, moderate staining; and 3, strong staining) and the percentage of positive staining (0, 0–5% positive area; 1, 6–25% positive area; 2, 26–50% positive area; 3, 51–75% positive area; and 4, 76–100% positive area) were recorded, and the total score was calculated by multiplying the two scores [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the functional status of MCs may be modulated by the female sex hormones E2 and progesterone P4 [ 3 ]. For example, NLRP3 inflammasome activation of MCs by estrogen via the nuclear-initiated signaling pathway contributes to the immune inflammatory response in endometriosis and further spreading of the disease [ 84 ]. MCs express E2 (ER α , ER β , and G protein-coupled estrogen receptor (GPER) and P4 receptors (PR-A and PR-B) and further respond to these hormones, which causes changes in MC cell number, distribution, and degranulation in ovarian tissue [ 3 , 85 ].…”
Section: Mcs and Mc-derived Mediators In A Woman's Reproductive Syste...mentioning
confidence: 99%
“…It was proposed that MCs represent a therapeutic target in endometriosis to assure better control of endometriosis inhibition and symptom relief [ 82 ]. Not surprisingly, endometriosis is included in the list of symptoms and findings in MCAS [ 76 , 84 ]. Despite the existence of undoubted dysfunction of the immune system in endometriosis, no evidence is available that shows that those with endometriosis are at an increased risk of contracting COVID-19.…”
Section: Covid-19-related Mcas or Nc-mcas And Possible Consequences F...mentioning
confidence: 99%